PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN TV BERLANGGANAN TRANSVISION DI KOTA BATAM - Kurniat Hati Mendrofa,; Yossi Hendriati, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This research is aimed to know the influence of price, product, and service qualities toward the purchase of cable or paid TV in Batam. The research uses description analysis method which gives the description of research object variables that have been researched and then takes the conclusion. The research objects as free variables are the price (X1), product quality (X2), service quality (X3) and purchase decision as tied variable. The population of the research is all the Transvision cable or paid TV subscibers in Batam. The sampling method uses purposive sampling technique means the samples decided by the resercher based on the subscribers who have subscribed more than 3 years, who takes gold package for a year and youngsters within 18-35 years old the samples of this research are 50 subscribers. Data processing shows the influence of the price, product quality and service quality toward the decision of Transvision cable TV purchasing in Batam. R square 80,7% from the result, can be concluded that the price variable (X1), product quality (X2), service quality (X3) influence simultaneously to the decision of purchasing variable (Y) However 19,3% influenced by other variables out of this  regression equation or the variables which not reserched by the writer